Has grey literature a value in conservation? The Case of Queñoa Polylepis spp. in Northwestern Argentina - Cuyckens, Griet An Erica (2024)
The Polylepis genus faces signicant conservation challenges, with all species experiencing declining population trends. Northwest Argentina, home to ve species, represents a hotspot, yet this region has received less research attention in the country. This review assesses the role of grey literature in Polylepis conservation, supplemented by eldwork. Our ndings reveal that most data focus on Polylepis tomentella, with less entries on P. australis, P. tarapacana, and especially P. hieronymi, and P. crista-galli. More than half of the information rated as useful for conservation purposes was provided by grey literature (51.8%). Locally informed population trends for P. australis oer valuable insights, though broader conclusions are still required. The available information was essential in identifying knowledge gaps and threats. This work underscores the need for eld experiments to validate prevailing assumptions about the genus. The information presented here provides a solid foundation for future conservation strategies and we recommend including grey literature in reviews on little-known species or underrepresented regions.